A method for producing aromatic hydrocarbons from carbon dioxide and dimethyl ether
By using carbon dioxide and dimethyl ether as raw materials and combining the modification technology of molecular sieve catalysts, the catalyst stability and economical problems in traditional aromatic hydrocarbon preparation processes are solved, and efficient and economical aromatic hydrocarbon production is achieved.
Patent Information
- Application Number
- CN202111506077.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-12-10
AI Technical Summary
The traditional methanol-making aromatic hydrocarbon process has problems such as short catalyst life, frequent regeneration, and low temporal and spatial yield, and its poor economic performance, which limits its industrial application.
Carbon dioxide and dimethyl ether are used as raw materials and reacted through molecular sieve catalysts to produce mixed aromatic hydrocarbons. The method includes preheating the feed gas and then passing through a reactor equipped with a catalyst bed to produce aromatic hydrocarbons. The catalyst is prepared by molecular sieve, oxide modification, silanization reagent modification and hydrothermal treatment.
The high selectivity of aromatic hydrocarbons (up to 98%) and catalyst stability are achieved, which reduces production costs and has good industrial application prospects.
Smart Images

Figure BDA0003404426560000181 
Figure BDA0003404426560000191
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing aromatic hydrocarbons from carbon dioxide and dimethyl ether, belonging to the field of chemistry and chemical engineering. Background Art
[0002] Mixed aromatics are colorless transparent liquids. Odor: special odor. It is an aromatic mixture obtained by extracting narrow-fraction reformed aromatics. It contains benzene, toluene, and xylene. It can be used as a raw material for petroleum resins, gasoline, and solvents. Mixed aromatics can be further subjected to transalkylation, alkylation, isomerization, and other processes to obtain paraxylene, which is polymerized with ethylene glycol produced from coal to form a complete industrial chain of polyester materials using coal as raw materials. In addition, hydrocarbon mixtures with an aromatic content greater than 65% can be directly used as a blending component for gasoline. At present, mixed aromatics on the market are mainly produced by the catalytic reforming process of petrochemicals. In view of the current energy structure of China, which is "rich in coal and poor in oil", it is of great significance to vigorously develop a process route for producing mixed aromatics using coal as a starting material.
[0003] Carbon dioxide is one of the important gas emissions in the chemical plant process. With the continuous enhancement of environmental awareness, for the sustainable development of social economy, the trend of reducing the increasing carbon dioxide in the atmosphere has attracted widespread attention from scientists around the world. The traditional route of preparing aromatics from coal to synthesis gas and methanol can be divided into two types: fluidized bed methanol to aromatics technology and fixed bed methanol to aromatics process technology. There is a contradiction of atomic balance when using methanol as raw material to produce aromatics. The carbon-hydrogen ratio of aromatics is low, and alkanes must be generated in the product to balance the lower carbon-hydrogen ratio in aromatics. In order to increase the yield of aromatics, a large amount of alkanes in the product must be dehydrogenated or cracked at a higher temperature, which will increase the equipment investment of the device and the operating cost of the methanol to aromatics process technology. Economic efficiency restricts the large-scale industrial application of methanol to aromatics technology. Summary of the invention
[0004] The object of the present invention is to provide a method for producing mixed aromatics from carbon dioxide and dimethyl ether. The method uses carbon monoxide and dimethyl ether as raw materials and molecular sieves as catalysts to produce mixed aromatics. The catalyst stability of the method is good, the space-time yield of the product mixed aromatics is high, the device is easy to achieve large-scale, and has good industrial application prospects. The process route for producing aromatics using carbon dioxide and dimethyl ether as raw materials overcomes the shortcomings of the traditional methanol-to-aromatics process route and has good economic efficiency. In addition, a large amount of carbon dioxide is produced as a by-product in the coal chemical process. How to effectively utilize the carbon dioxide in the waste gas and improve the economic efficiency is a difficult problem faced by scientific researchers. The preparation of dimethyl ether from coal via synthesis gas is a mature technology. The device for synthesizing aromatics using carbon dioxide and dimethyl ether as raw materials is not restricted by raw materials and is easy to achieve large-scale. The preparation of mixed aromatics using carbon dioxide and dimethyl ether as raw materials is a process route with good economic efficiency and has good industrial application prospects.
[0005] As one aspect of the present application, a method for producing aromatics from carbon dioxide and dimethyl ether is provided, comprising the following steps:
[0006] Passing a raw gas containing carbon dioxide and dimethyl ether into a reactor to contact with a catalyst for reaction to obtain the aromatic hydrocarbons;
[0007] The catalyst is obtained by molding a material containing a molecular sieve and a binder, calcining it, and modifying it;
[0008] The modification includes oxide i modification, silanization agent modification and hydrothermal treatment.
[0009] Optionally, the molar ratio of carbon dioxide to dimethyl ether is 0.5:1-20:1.
[0010] Optionally, the molar ratio of carbon dioxide to dimethyl ether is any one of 0.5:1, 1:1, 3:1, 5:1, 8:1, 10:1, 12:1, 15:1, 16:1, 18:1, 20:1, or a range between any two values.
[0011] Optionally, the feed weight space velocity of dimethyl ether is 0.3-10h -1 .
[0012] Optionally, the feed weight space velocity of dimethyl ether is 0.3h -1 , 0.5h -1 , 1h -1 , 3h -1 , 5h -1 , 7h -1 , 8h -1 , 10h -1 Any value or a range of values between any two values.
[0013] Optionally, the reaction temperature is 400-600°C.
[0014] Optionally, the reaction temperature is any one of 400°C, 420°C, 430°C, 450°C, 460°C, 470°C, 490°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C or a range between any two values.
[0015] Optionally, the reaction pressure is 0.2-10.0 MPa.
[0016] Optionally, the reaction pressure is any one of 0.2 MPa, 0.5 MPa, 0.8 MPa, 1 MPa, 2 MPa, 3 MPa, 5 MPa, 6 MPa, 8 MPa, and 10 MPa, or a range between any two values.
[0017] Optionally, the molecular sieve includes at least one of ZSM-5 molecular sieve, MCM-22 molecular sieve, and MCM-49 molecular sieve.
[0018] Optionally, the molecular sieve has a molar silicon-to-aluminum ratio of 20-500.
[0019] Optionally, the molecular sieve has a molar silicon-to-aluminum ratio of any one of 20, 30, 40, 50, 70, 80, 90, 100, 150, 200, 240, 260, 280, 300, 350, 400, 450, and 500, or a range between any two of the values.
[0020] Optionally, the molecular sieve is a hydrogen type molecular sieve or an ammonium type molecular sieve.
[0021] Optionally, the molecular sieve content in the catalyst is 30-85wt%.
[0022] Optionally, the molecular sieve content in the catalyst is any one of 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 85wt% or a range value between any two values.
[0023] Optionally, the binder includes at least one of boehmite, alumina, diatomaceous earth, silica, and kaolin.
[0024] Optionally, the binder is a modified binder modified by peroxide ii.
[0025] Optionally, the oxide II in the oxide II modification includes at least one of magnesium oxide, calcium oxide, zirconium oxide, zinc oxide, chromium oxide and nickel oxide.
[0026] Optionally, the content of magnesium oxide, calcium oxide, zirconium oxide, zinc oxide, chromium oxide and nickel oxide in the modified binder is independently 1-25 wt %.
[0027] Optionally, the content of magnesium oxide, calcium oxide, zirconium oxide, zinc oxide, chromium oxide and nickel oxide in the modified binder is independently any one of 1wt%, 3wt%, 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 17wt%, 19wt%, 23wt%, 25wt% or a range value between any two values.
[0028] Optionally, the calcination i is calcination at 550° C.-700° C. for 4-10 hours.
[0029] Optionally, the oxide i in the oxide i modification includes at least one of magnesium oxide, calcium oxide, zirconium oxide, zinc oxide, chromium oxide and nickel oxide.
[0030] Optionally, the content of magnesium oxide, calcium oxide, zirconium oxide, zinc oxide, chromium oxide and nickel oxide in the catalyst is independently 1-15 wt %.
[0031] Optionally, the content of magnesium oxide, calcium oxide, zirconium oxide, zinc oxide, chromium oxide and nickel oxide in the catalyst is independently any one of 1wt%, 3wt%, 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 17wt%, 19wt%, 23wt%, 25wt% or a range value between any two values.
[0032] Optionally, the silanization agent modification comprises the following steps:
[0033] The catalyst is impregnated with a silanization agent solution and calcined ii.
[0034] Optionally, the silanization agent in the silanization agent solution includes at least one of ethyl orthosilicate, benzyl silicone oil, and dimethyl silicone oil.
[0035] Optionally, the solvent in the silanization agent solution includes cyclohexane and / or n-hexane.
[0036] Optionally, the silanization agent content in the silanization agent solution is 20-50 wt %.
[0037] Optionally, the content of the silanizing agent in the silanizing agent solution is any one of 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt% or a range value between any two values.
[0038] Optionally, the immersion time is 2-24 hours.
[0039] Optionally, the immersion time is any one of 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 13 hours, 15 hours, 18 hours, 20 hours, and 24 hours, or a range value between any two values.
[0040] Optionally, the calcination ii is performed at 550° C.-700° C. in an air atmosphere for 1-10 hours.
[0041] Optionally, the hydrothermal treatment comprises:
[0042] The catalyst was hydrothermally treated in aqueous ammonia solution.
[0043] Optionally, the concentration of the aqueous ammonia solution is 5-10 wt %.
[0044] Optionally, the hydrothermal treatment is performed at a temperature of 60° C. to 180° C. for 10 to 24 hours.
[0045] Optionally, the temperature of the hydrothermal treatment is any one of 60°C, 80°C, 100°C, 120°C, 150°C, 180°C, or a range between any two of the values.
[0046] The time can be any value among 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 24 hours, or a range between any two values.
[0047] As an implementation scheme, the present application provides a method for producing aromatic hydrocarbons from carbon dioxide and dimethyl ether, with carbon dioxide gas and dimethyl ether as raw materials; the raw gas is preheated and continuously passed through a reactor equipped with a catalyst bed to react and generate aromatic hydrocarbons; the aromatic hydrocarbon selectivity is as high as 98%, the catalyst has good stability, and has good industrial application prospects.
[0048] The technical problem to be solved by this application is that the traditional methanol to aromatics production technology has the disadvantages of short catalyst life, frequent catalyst regeneration, low aromatics space-time yield, etc. The present invention provides a method for producing mixed aromatics from carbon dioxide and dimethyl ether, which uses carbon dioxide and dimethyl ether as raw materials to produce mixed aromatics on a molecular sieve catalyst with high selectivity, with a simple process and good economy.
[0049] To solve the above problems, the technical solution adopted by the present invention is as follows:
[0050] A method for producing aromatic hydrocarbons from carbon dioxide and dimethyl ether, wherein carbon dioxide and dimethyl ether raw gas are preheated and then continuously passed through a reactor equipped with a catalyst bed to produce aromatic hydrocarbons under given reaction conditions;
[0051] The catalyst comprises a molecular sieve and an oxide-modified binder, which are mixed and formed, and then modified with an oxide and a silanization agent and subjected to hydrothermal treatment.
[0052] The reaction conditions are:
[0053] The reaction temperature is 400-600°C;
[0054] The reaction pressure is 0.2-10.0MPa;
[0055] The molar ratio of carbon dioxide to dimethyl ether is 0.5:1-20:1;
[0056] Feed dimethyl ether weight space velocity 0.3-10h -1 ;
[0057] The reaction conditions are preferably:
[0058] The reaction temperature is 420-550°C;
[0059] Dimethyl ether feed weight space velocity 1-10h -1 .
[0060] The molecular sieve is a combination of one or more of ZSM-5, MCM-22 and MCM-49 molecular sieves, and the molecular sieve molar silicon-aluminum ratio is 20-500.
[0061] The molecular sieve is a hydrogen type or an ammonium type molecular sieve, and its content is 30-85%.
[0062] The binder is one or more of boehmite, alumina, diatomaceous earth, silicon oxide or kaolin.
[0063] The oxide modification of the binder and the oxide modification of the catalyst after forming are composite modifications of one or more oxides in the oxide.
[0064] The oxide modified in the binder and the oxide modified in the catalyst after forming is one of magnesium oxide, calcium oxide and zirconium oxide, with a weight content of 1-15%.
[0065] The oxide modified in the binder and the oxide modified in the catalyst after forming is one of zinc oxide, chromium oxide or nickel oxide, with a weight content of 1-10%.
[0066] The silanization agent is one or more of ethyl orthosilicate, benzyl silicone oil and dimethyl silicone oil.
[0067] The catalyst preparation process comprises the following steps:
[0068] (1) modifying the binder into oxide, drying, and calcining at 550° C. to 700° C. for 3 to 10 hours;
[0069] (2) mixing the oxide-modified binder and the molecular sieve in step (1), drying, and calcining at 550° C.-700° C. for 4-10 hours;
[0070] (3) the shaped catalyst obtained in step (2) is further subjected to oxide modification, drying, and calcining at 550° C.-700° C. for 3-10 hours;
[0071] (4) using an equal volume impregnation method, immersing the catalyst obtained in step (3) in a solution of a silanization agent at room temperature for 2-24 hours, and calcining at 550° C.-700° C. in an air atmosphere for 1-10 hours; cooling to room temperature, and repeating the above steps 1-3 times to obtain a silanization agent modified catalyst;
[0072] (5) The catalyst prepared in step (3) is treated hydrothermally, dried, and calcined at 500° C.-800° C. for 2-10 hours to obtain the catalyst.
[0073] The solution of the silanization agent is a cyclohexane solution or a normal hexane solution of the silanization agent, or a mixture of the two.
[0074] The weight percentage of the silanization agent in the silanization agent solution is 20%-50%.
[0075] The hydrothermal treatment process is as follows: placing the prepared catalyst in a closed autoclave, the weight ratio of the catalyst to the ammonia solution is 1:10, and the weight concentration of the ammonia solution is 5%-10%; the treatment temperature is 60°C-180°C, and the time is 10-24 hours.
[0076] According to different molding methods, it can be used as a fluidized bed catalyst or a fixed bed catalyst. After spray molding, the fluidized bed catalyst can be obtained through the above preparation steps. The fixed bed catalyst can be obtained by extruding into a matrix through the above steps.
[0077] It is necessary to further explain here that the preparation process takes into account the characteristics of the catalyst structure and the number of acid sites, optimizes and controls the modification steps and the percentage of modifiers in the catalyst, and uses modified silicon oxide, diatomaceous earth, alumina, and kaolin for calcination to achieve selective modulation of the catalyst acidity. The carrier or molecular sieve has dehydrogenation activity after being modified with oxides, and water vapor treatment modulates the acid sites of the catalyst, changes the pores of the catalyst, and enhances the hydrothermal stability of the catalyst. It is the synergistic effect of these modification processes that makes the catalyst a dual-functional catalyst with good acid catalysis and dehydrogenation functions, which can fully meet the requirements of industrial use.
[0078] The catalyst preparation process is to mix and form molecular sieves and adhesives, and the forming method can be spray drying or extrusion molding. The molecular sieve can be hydrogen or ammonia type ZSM-5, MCM-22 and MCM-49 molecular sieves. The weight content of oxide modification is 1%-15%. The hydrothermal treatment temperature is preferably 60℃-180℃, and 10% ammonia solution is treated for 10-24 hours. The reagent used for silanization is benzyl silicone oil or dimethyl silicone oil, and the solvent is n-hexane or cyclohexane. The prepared solution of organic silicon compound needs to be fully shaken, shaken, and left to stand overnight. Each step of silanization affects the effect of silanization. Silanization treatment selectively modulates the acidic site of the outer surface and improves the para-selectivity.
[0079] It should be further explained that carbon dioxide and dimethyl ether are used as raw materials to continuously pass through a reactor equipped with a catalyst bed to produce aromatics. A small amount of methane, ethane and ethylene in the reaction product can be used as boiler fuel gas as dry gas, and carbon three and carbon five components are used as liquefied gas, the total of which is less than 1%. The production of aromatics with carbon dioxide and dimethyl ether has high aromatic selectivity and simple process, which is an ideal process route for coal-to-aromatics.
[0080] It should be noted that the various modification methods of the catalyst are different according to the acid strength of the parent molecular sieve and the density of different acid sites. The various modification methods used in this application are combined to obtain the desired catalyst. For a molecular sieve parent with a smaller acid site density of the catalyst, one or two modification methods of this application can be used to obtain the ideal acid strength. Therefore, single modification methods of various elements also fall within the scope of this application. For example, single modifications such as metal oxide modification, acid treatment, and water vapor treatment all fall within the scope of this application.
[0081] The beneficial effects of this application include but are not limited to:
[0082] (1) The present application provides a method for producing aromatics from carbon dioxide and dimethyl ether, with high space-time yield of aromatics and good catalyst stability;
[0083] (2) The method for producing aromatics provided in the present application has the characteristics of simple production process, few reaction by-products, and high raw material utilization rate. Compared with the traditional methanol to aromatics production process, it can significantly reduce production costs and has good economic benefits. DETAILED DESCRIPTION
[0084] The present invention is further described below with reference to the embodiments.
[0085] The MCM-49 molecular sieve in the examples is synthesized according to the method in USP5236575. The MCM-22 molecular sieve in the examples is synthesized according to the method in USP4954325. ZSM-5 molecular sieve is produced by the catalyst factory of Nankai University, and its product name is NKF-5II.
[0086] Example 1
[0087] The preparation process of the catalyst is as follows: 26.3 grams of chromium nitrate nonahydrate is added to 100 grams of deionized water to dissolve, 75 grams of diatomaceous earth is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 600°C for 10 hours to obtain 80 grams of modified diatomaceous earth (chromium oxide weight content is 6.25%). 120 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 20 is mixed with 80 grams of modified diatomaceous earth, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid for extrusion molding.
[0088] Dry at 120°C and calcine at 500°C for 10 hours. The above catalyst is cut into 1-3mm to obtain a columnar catalyst matrix A0. 20 grams of A0 sample is impregnated with zinc nitrate and nickel nitrate aqueous solution (zinc nitrate mass content is 14%, nickel nitrate mass content is 5.84%) for 12 hours, dried at 120°C, and calcine at 600°C for 3 hours. The weight content of zinc oxide is 3% and the weight content of nickel oxide is 1.5% to obtain A1. 10g of cyclohexane solution of 20% by weight benzyl silicone oil is added to 20g of A1, immersed at room temperature for 10 hours, dried at 120°C, and calcine at 550°C for 10 hours to obtain A2. 10g of cyclohexane solution of 20% by weight benzyl silicone oil is added to 20g of A2 and immersed at room temperature for 12 hours. The calcination procedure is the same as A2 to obtain A3. 20 g of A3 was placed in an autoclave containing 200 g of 5% ammonia solution, sealed, and subjected to hydrothermal treatment for 10 hours at 60°C and calcined at 550°C for 3 hours to obtain catalyst A. The molecular sieve content was 60 wt%.
[0089] Example 2
[0090] The preparation process of the catalyst is as follows: 52.7 grams of chromium nitrate nonahydrate is added to 200 grams of deionized water to dissolve, 130 grams of alumina is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 700°C for 10 hours to obtain 140 grams of modified alumina (chromium oxide weight content is 7.14%). 60 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 30 is mixed with 100 grams of silica sol with a weight content of 40% by weight of silicon dioxide and 140 grams of modified alumina, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0091] Dry at 120°C and calcine at 700°C for 4 hours. The above catalyst is cut into 1-3mm pieces to obtain a columnar catalyst matrix B0. 20 grams of B0 sample is impregnated with a zirconium nitrate aqueous solution (mass content of zirconium nitrate is 52.3%) for 12 hours, dried at 120°C, calcined at 550°C for 10 hours, and the weight content of zirconium oxide is 15% to obtain B1. 10g of a cyclohexane solution of dimethyl silicone oil with a weight content of 50% is added to 20 grams of B1, immersed at room temperature for 8 hours, dried at 120°C, and calcined at 550°C for 10 hours to obtain B2. 10g of a cyclohexane solution of ethyl orthosilicate with a weight content of 30% is added to 20 grams of B2 and immersed at room temperature for 8 hours. The calcination procedure is the same as that of B2 to obtain B3. 20 grams of B3 sample was immersed in magnesium nitrate aqueous solution (magnesium nitrate mass content was 3.71%) for 12 hours, dried at 120°C, calcined at 550°C for 10 hours, and the weight content of magnesium oxide was 1% to obtain B4. 20 grams of B4 was placed in an autoclave containing 200 grams of 8% ammonia solution, sealed, and hydrothermally treated for 12 hours at 80°C, and calcined at 600°C for 3 hours to obtain catalyst B. The molecular sieve content in the catalyst was 30wt%.
[0092] Example 3
[0093] The preparation process of the catalyst is as follows: 19.5 grams of nickel nitrate hexahydrate is added to 100 grams of deionized water to dissolve, 20 grams of diatomaceous earth and 25 grams of kaolin are added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 700°C for 10 hours to obtain 50 grams of modified binder (nickel oxide weight content is 10%). 200 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 100 is mixed with the above binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0094] Dry at 120°C and calcine at 550°C for 4 hours. The above catalyst is cut into 1-3mm pieces to obtain a columnar catalyst matrix D0. 20 grams of D0 sample is impregnated with an aqueous solution of zinc nitrate and chromium nitrate (the mass content of zinc nitrate is 14.6% and the mass content of chromium nitrate is 15.8%) for 24 hours, dried at 120°C, and calcined at 600°C for 3 hours. The weight percentage of zinc oxide in the catalyst is 4%, and the weight percentage of chromium oxide is 3%, to obtain D1. 10g of a cyclohexane solution of 40% by weight of tetraethyl orthosilicate is added to 20g of D1, immersed at room temperature for 12 hours, dried at 120°C, and calcined at 550°C for 10 hours to obtain D2. 10g of a cyclohexane solution of 20% by weight of benzyl silicone oil is added to 20g of D2, and immersed at room temperature for 12 hours. The calcination procedure is the same as that of D2 to obtain D3. 20 g of D3 was placed in an autoclave containing 200 g of 10% ammonia solution, sealed, and hydrothermally treated for 15 hours at 120° C., and calcined at 650° C. for 3 hours to obtain catalyst D. The molecular sieve content in the obtained catalyst was 80 wt%.
[0095] Example 4
[0096] The preparation process of the catalyst is as follows: 39 grams of nickel nitrate hexahydrate are added to 200 grams of deionized water to dissolve, 20 grams of diatomaceous earth and 20 grams of alumina are added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 700°C for 10 hours to obtain 50 grams of modified binder (with a nickel oxide weight content of 20%). 200 grams of ammonia-type ZSM-5 molecular sieve with a molar silicon-aluminum ratio of 50 is mixed with 50 grams of the above-mentioned modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0097] Dry at 120°C and calcine at 550°C for 4 hours. The above catalyst is cut into 1-3mm to obtain a columnar catalyst matrix E0. 20 grams of E0 sample is impregnated with zinc nitrate and calcium nitrate aqueous solution (zinc nitrate mass content is 36.6%, calcium nitrate mass content is 12.7%) for 24 hours, dried at 120°C, calcine at 650°C for 3 hours, the weight content of zinc oxide is 10%, and the weight content of calcium oxide is 3%, to obtain E1. 10g of cyclohexane solution of 40% by weight of tetraethyl orthosilicate is added to 20g of E1, immersed at room temperature for 6 hours, dried at 120°C, and calcine at 550°C for 10 hours to obtain E2. 10g of cyclohexane solution of 35% by weight of tetraethyl orthosilicate is added to 20g of E2 and immersed at room temperature for 6 hours. The calcination procedure is the same as that of E2 to obtain E3. 10 g of cyclohexane solution of 30% by weight of tetraethyl orthosilicate was added to 20 g of E3 and immersed at room temperature for 2 hours. The calcination procedure was the same as that of E2 to obtain E4. 20 g of E4 was placed in an autoclave containing 200 g of 6% ammonia solution, sealed and hydrothermally treated for 12 hours at a temperature of 150°C, and calcined at 550°C for 3 hours to obtain catalyst E. The molecular sieve content in the obtained catalyst was 80 wt%.
[0098] Example 5
[0099] The preparation process of the catalyst is as follows: 21 grams of calcium nitrate tetrahydrate is added to 200 grams of deionized water to dissolve, 20 grams of diatomaceous earth and 25 grams of alumina are added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 650°C for 10 hours to obtain 50 grams of modified binder (calcium oxide weight content is 10%). 200 grams of ammonia-type ZSM-5 molecular sieve with a molar silicon-aluminum ratio of 150 is mixed with the above-mentioned 50 grams of modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0100] Dry at 120°C and calcine at 550°C for 4 hours. The above catalyst is cut into 1-3 mm pieces to obtain a columnar catalyst matrix F0. 20 grams of F0 sample is impregnated with hexahydrate zinc nitrate and hexahydrate nickel nitrate aqueous solution (zinc nitrate mass content is 10.97%, nickel nitrate mass content is 7.78%) for 24 hours, dried at 120°C, and calcined at 650°C for 3 hours. The weight content of zinc oxide is 3%, and the weight content of nickel oxide is 2%, to obtain F1. 10g of cyclohexane solution of 40% by weight of tetraethyl orthosilicate is added to 20g of F1, immersed at room temperature for 24 hours, dried at 120°C, and calcined at 550°C for 10 hours to obtain F2. 10g of cyclohexane solution of 35% by weight of tetraethyl orthosilicate is added to 20g of F2, and immersed at room temperature for 24 hours. The calcination procedure is the same as that of F2 to obtain F3. 10 g of cyclohexane solution of 30% by weight of tetraethyl orthosilicate was added to 20 g of F3 and immersed at room temperature for 2 hours. F4 was obtained by the same calcination procedure as F2. 20 g of F4 was placed in an autoclave containing 200 g of 8% ammonia solution, sealed and hydrothermally treated for 18 hours at a temperature of 160°C and calcined at 550°C for 3 hours to obtain catalyst F. The molecular sieve content in the obtained catalyst was 80 wt%.
[0101] Example 6
[0102] The preparation process of the catalyst is as follows: 42 grams of calcium nitrate tetrahydrate is added to 200 grams of deionized water to dissolve, 40 grams of boehmite is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 600°C for 10 hours to obtain 50 grams of modified binder (calcium oxide weight content is 20%). 200 grams of ammonia-type ZSM-5 molecular sieve with a molar silicon-aluminum ratio of 200 is mixed with the above-mentioned 50 grams of modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0103] Dry at 120°C and calcine at 550°C for 4 hours. The above catalyst is cut into 1-3mm to obtain a columnar catalyst matrix G0. 20 grams of G0 sample is impregnated with zinc nitrate and magnesium nitrate aqueous solution (zinc nitrate mass content is 36.6%, magnesium nitrate mass content is 11.2%) for 36 hours, dried at 120°C, calcine at 600°C for 3 hours, the weight content of zinc oxide is 10%, and the weight content of magnesium oxide is 3%, to obtain G1. 10g of n-hexane solution of 35% by weight of tetraethyl orthosilicate is added to 20g of G1, immersed at room temperature for 2 hours, dried at 120°C, and calcine at 550°C for 10 hours to obtain G2. 10g of n-hexane solution of 30% by weight of tetraethyl orthosilicate is added to 20g of G2 and immersed at room temperature for 2 hours. The calcination procedure is the same as G2 to obtain G3. 20 g of G3 was placed in an autoclave containing 10% ammonia solution, sealed, and hydrothermally treated for 18 hours at 100° C., and calcined at 650° C. for 3 hours to obtain catalyst G. The molecular sieve content in the obtained catalyst was 80 wt%.
[0104] Example 7
[0105] The preparation process of the catalyst is as follows: 21.1 grams of calcium nitrate tetrahydrate is added to 100 grams of deionized water to dissolve, 55 grams of kaolin is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 700°C for 10 hours to obtain 60 grams of modified binder (calcium oxide weight content is 8.3%). 140 grams of ammonia-type ZSM-5 molecular sieve with a molar silicon-aluminum ratio of 200 is mixed with 50 grams of the above-mentioned modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0106] Dry at 120°C and calcine at 550°C for 4 hours. The above catalyst is cut into 1-3mm pieces to obtain a columnar catalyst matrix H0. 20 grams of H0 sample is impregnated with chromium nitrate and zirconium nitrate aqueous solution (chromium nitrate mass content is 52.6%, zirconium nitrate mass content is 10.45%) for 20 hours, dried at 120°C, calcine at 650°C for 4 hours, the weight content of chromium oxide is 10%, and the weight content of zirconium oxide is 3%, to obtain H1. 10g of a 35% by weight dimethyl silicone oil n-hexane solution is added to 20g of H1, immersed at room temperature for 4 hours, dried at 120°C, and calcine at 550°C for 10 hours to obtain H2. 10g of a 20% by weight dimethyl silicone oil n-hexane solution is added to 20g of H2, and immersed at room temperature for 4 hours. The calcination procedure is the same as that of H2 to obtain H3. 20 g of H3 was placed in an autoclave containing 200 g of 7% ammonia solution, sealed, and hydrothermally treated for 24 hours at a temperature of 180°C, and calcined at 550°C to obtain catalyst H. The molecular sieve content in the obtained catalyst was 70 wt%.
[0107] Example 8
[0108] The preparation process of the catalyst is as follows: 18.3 grams of zinc nitrate hexahydrate is added to 100 grams of deionized water to dissolve, 25 grams of diatomaceous earth is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 700°C for 10 hours to obtain 30 grams of modified binder (with a zinc oxide weight content of 16.7%). 170 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 30 is mixed with 30 grams of the above-mentioned modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0109] Dry at 120°C and calcine at 550°C for 4 hours. The above catalyst is cut into 1-3mm to obtain a columnar catalyst matrix I0. 20 grams of I0 sample is immersed in a calcium nitrate aqueous solution (calcium nitrate mass content is 12.65%) for 24 hours, dried at 120°C, calcine at 700°C for 5 hours, and the calcium oxide weight content is 3% to obtain I1. 10g of a n-hexane solution of dimethyl silicone oil with a weight content of 35% is added to 20 grams of I1, immersed at room temperature for 4 hours, dried at 120°C, and calcine at 550°C for 10 hours to obtain I2. 10g of a n-hexane solution of dimethyl silicone oil with a weight content of 20% is added to 20 grams of I2, immersed at room temperature for 4 hours. The calcination procedure is the same as that of I2 to obtain I3. 20 grams of I3 are placed in an autoclave filled with 9% ammonia solution, sealed and hydrothermally treated for 10 hours at a treatment temperature of 160°C, and calcined at 550°C for 3 hours to obtain catalyst I. The content of molecular sieve in the prepared catalyst is 85wt%.
[0110] Example 9
[0111] The preparation process of the catalyst is as follows: 26.4 grams of chromium nitrate nonahydrate is added to 100 grams of deionized water to dissolve, 35 grams of aluminum oxide is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 550°C for 10 hours to obtain 40 grams of a modified binder (chromium oxide weight content is 12.5%). 160 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 300 is mixed with the above-mentioned 40 grams of the modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0112] Dry at 120°C and calcine at 550°C for 4 hours. The above catalyst is cut into 1-3mm to obtain a columnar catalyst matrix J0. 20 grams of J0 sample is impregnated with zirconium nitrate solution (mass content of zirconium nitrate is 52.3%) for 24 hours, dried at 120°C, calcine at 700°C for 3 hours, and the weight content of zirconium oxide is 15% to obtain J1. 10g of n-hexane solution of 40% by weight of tetraethyl orthosilicate is added to 20g of J1, immersed at room temperature for 2 hours, dried at 120°C, and calcine at 550°C for 10 hours to obtain J2. 10g of n-hexane solution of 30% by weight of tetraethyl orthosilicate is added to 20g of J2 and immersed at room temperature for 2 hours. The calcination procedure is the same as that of J2 to obtain J3. 20 grams of J3 sample was immersed in magnesium nitrate solution (magnesium nitrate mass content was 7.42%) for 24 hours, dried at 120°C, calcined at 600°C for 3 hours, and the weight content of magnesium oxide was 2% to obtain J4. 20 grams of J4 was placed in a 200-gram autoclave filled with 8% ammonia solution, sealed, and hydrothermally treated for 16 hours at a treatment temperature of 150°C, and calcined at 550°C for 3 hours to obtain catalyst J. The content of molecular sieve in the obtained catalyst was 80wt%.
[0113] Example 10
[0114] The preparation process of the catalyst is as follows: 52.6 grams of chromium nitrate nonahydrate is added to 200 grams of deionized water to dissolve, 30 grams of aluminum oxide is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 600°C for 10 hours to obtain 40 grams of modified binder (chromium oxide weight content is 25%). 160 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 400 is mixed with the above-mentioned modified binder 40, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0115] Dry at 120℃ and calcine at 550℃ for 4 hours. The above catalyst was cut into 1-3mm to obtain a columnar catalyst matrix K0. 20 grams of K0 sample was impregnated with nickel nitrate and zirconium nitrate aqueous solution (nickel nitrate mass content is 11.67%, zirconium nitrate mass content is 10.45%) for 24 hours, dried at 120℃, calcine at 600℃ for 3 hours, nickel oxide weight content is 3%, zirconium oxide weight content is 3%, and K1 was obtained. 10g of n-hexane solution of 40% by weight of ethyl orthosilicate was added to 20g of K1, immersed at room temperature for 2 hours, dried at 120℃, and calcine at 550℃ for 10 hours to obtain K2. 10g of n-hexane solution of 30% by weight of dimethyl silicone oil was added to 20g of K2, immersed at room temperature for 2 hours, and dried at 120℃. The calcination procedure is the same as K2 to obtain K3. 20 g of K3 was placed in an autoclave containing 200 g of 5% ammonia solution, sealed, and hydrothermally treated for 20 hours at 180°C, and calcined at 650°C for 5 hours to obtain catalyst K. The molecular sieve content in the obtained catalyst was 80 wt%.
[0116] Embodiment 11
[0117] The preparation process of the catalyst is as follows: 26.3 grams of chromium nitrate nonahydrate is added to 100 grams of deionized water to dissolve, 35 grams of aluminum oxide is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 600°C for 10 hours to obtain 40 grams of a modified binder (chromium oxide weight content is 12.5%). 160 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 500 is mixed with the above-mentioned 40 grams of the modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0118] Dry at 120℃ and calcine at 550℃ for 4 hours. The above catalyst was cut into 1-3mm to obtain a columnar catalyst matrix L0. 20 grams of L0 sample was impregnated with an aqueous solution of calcium nitrate and magnesium nitrate (calcium nitrate mass content is 21.08%, magnesium nitrate mass content is 7.41%) for 24 hours, dried at 120℃, and calcine at 600℃ for 3 hours. The weight content of calcium oxide was 5% and the weight content of magnesium oxide was 2%, and L1 was obtained. 10g of cyclohexane solution of 40% benzyl silicone oil by weight was added to 20 grams of L1, immersed at room temperature for 2 hours, dried at 120℃, and calcine at 550℃ for 10 hours to obtain L2. 10g of n-hexane solution of 30% dimethyl silicone oil by weight was added to 20 grams of L2, immersed at room temperature for 2 hours, and dried at 120℃. The calcination procedure was the same as that of L2 to obtain L3. 20 g of L3 was placed in an autoclave filled with 10% ammonia solution, sealed, and hydrothermally treated for 18 hours at 150° C., and calcined at 550° C. for 3 hours to obtain catalyst L. The molecular sieve content in the obtained catalyst was 80 wt%.
[0119] Example 12
[0120] The preparation process of the catalyst is as follows: 26.3 grams of chromium nitrate nonahydrate is added to 100 grams of deionized water to dissolve, 25 grams of kaolin is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 600°C for 10 hours to obtain 30 grams of a modified binder (chromium oxide weight content is 16.7%). 100 grams of HMCM-22 molecular sieve with a molar silicon-aluminum ratio of 20 and 70 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 30 are mixed with the above-mentioned 30 grams of the modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0121] Dry at 120°C and calcine at 550°C for 4 hours. The above catalyst is cut into 1-3mm to obtain a columnar catalyst matrix M0. 20 grams of M0 are impregnated with an aqueous zinc nitrate solution (the mass content of zinc nitrate is 11%) for 24 hours, dried at 120°C, and calcined at 600°C for 3 hours, and the weight content of zinc oxide is 3%, thereby obtaining M1. 10g of a cyclohexane solution of 50% benzyl silicone oil by weight is added to 20 grams of M1, impregnated at room temperature for 2 hours, dried at 120°C, and calcined at 550°C for 10 hours to obtain M2. 20 grams of M2 are impregnated with an aqueous magnesium nitrate solution (the mass content of magnesium nitrate is 55.6%) for 24 hours, dried at 120°C, and calcined at 600°C for 3 hours, and the weight content of magnesium oxide is 15%, and calcined at 650°C for 3 hours to obtain catalyst M. The content of molecular sieve in the obtained catalyst is 85wt%.
[0122] Embodiment 13
[0123] The preparation process of the catalyst is as follows: 26.3 grams of chromium nitrate nonahydrate is added to 100 grams of deionized water to dissolve, 25 grams of diatomaceous earth is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 600°C for 10 hours to obtain 30 grams of a modified binder (chromium oxide weight content is 16.7%). 70 grams of HMCM-22 molecular sieve with a molar silicon-aluminum ratio of 60 and 100 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 300 are mixed with the above-mentioned 30 grams of the modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0124] Dry at 120℃ and calcine at 550℃ for 4 hours. The above catalyst was cut into 1-3mm to obtain a columnar catalyst matrix N0. 20 grams of N0 sample was impregnated with an aqueous solution of calcium acetate and zirconium nitrate solution (calcium acetate mass content is 6.29%, zirconium nitrate mass content is 20.9%) for 10 hours, dried at 120℃, and calcinated at 650℃ for 3 hours. The weight content of calcium oxide was 2% and the weight content of zirconium oxide was 6%, and N1 was obtained. 10g of cyclohexane solution of 40% by weight of ethyl orthosilicate was added to 20g of N1, immersed at room temperature for 2 hours, dried at 120℃, and calcinated at 550℃ for 10 hours to obtain N2. 10g of cyclohexane solution of 20% by weight of dimethyl silicone oil was added to 20g of N2, immersed at room temperature for 2 hours, and dried at 120℃. The calcination procedure was the same as that of N2 to obtain N3. 20 g of N3 was placed in an autoclave containing 200 g of 8% ammonia solution, sealed, and hydrothermally treated for 15 hours at a temperature of 160° C., and calcined at 650° C. for 3 hours to obtain catalyst N. The molecular sieve content in the obtained catalyst was 85 wt%.
[0125] Embodiment 14
[0126] The preparation process of the catalyst is as follows: 21 grams of calcium nitrate tetrahydrate is added to 100 grams of deionized water to dissolve, 25 grams of aluminum oxide is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 600°C for 10 hours to obtain 30 grams of a modified binder (calcium oxide weight content is 16.7%). 70 grams of HMCM-49 molecular sieve with a molar silicon-aluminum ratio of 50 and 100 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 400 are mixed with the above-mentioned 30 grams of the modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0127] Dry at 120℃ and calcine at 550℃ for 4 hours. The above catalyst was cut into 1-3mm to obtain a columnar catalyst matrix P0. 20 grams of P0 sample was soaked in chromium nitrate and zinc nitrate aqueous solution (chromium nitrate mass content is 10.5%, zinc nitrate mass content is 18.28%) for 36 hours, dried at 120℃, and calcine at 600℃ for 3 hours. The weight content of chromium oxide is 2% and the weight content of zinc oxide is 5%, and P1 is obtained. 10g of cyclohexane solution of 30% benzyl silicone oil by weight was added to 20g of P1, immersed at room temperature for 2 hours, dried at 120℃, and calcine at 550℃ for 10 hours to obtain P2. 10g of cyclohexane solution of 30% dimethyl silicone oil by weight was added to 20g of P2, immersed at room temperature for 2 hours, and dried at 120℃. The calcination procedure is the same as P2 to obtain P3. 20 g of P3 was placed in an autoclave containing 200 g of 10% ammonia solution, sealed, and hydrothermally treated for 14 hours at 170°C and calcined at 550°C for 3 hours to obtain catalyst P. The molecular sieve content in the obtained catalyst was 85 wt%.
[0128] Embodiment 15
[0129] The preparation process of the catalyst is as follows: 21.1 grams of calcium nitrate tetrahydrate is added to 100 grams of deionized water to dissolve, 35 grams of diatomaceous earth is added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 600°C for 10 hours to obtain 40 grams of modified binder (calcium oxide weight content is 12.5%). 60 grams of HMCM-22 molecular sieve with a molar silicon-aluminum ratio of 40 and 160 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 500 are mixed with the above-mentioned 40 grams of modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form strips.
[0130] Dry at 120℃ and calcine at 550℃ for 4 hours. The above catalyst was cut into 1-3mm columnar catalyst matrix R0. Dry at 120℃ and calcine at 500℃ for 2 hours to obtain R0. Add 10g of n-hexane solution of 40% by weight of ethyl orthosilicate to 20g of R1, soak at room temperature for 2 hours, dry at 120℃, and calcine at 550℃ for 10 hours to obtain R2. Add 10g of cyclohexane solution of 30% by weight of benzyl silicone oil to 20g of R2, soak at room temperature for 2 hours, and dry at 120℃. The calcination procedure is the same as R2 to obtain R3. 20g of R3 sample was impregnated with magnesium nitrate solution (magnesium nitrate mass content of 37.08%) for 20 hours, dried at 120℃, calcine at 700℃ for 3 hours, magnesium oxide weight content was 10%, and calcine at 550℃ for 3 hours to obtain catalyst R. The content of molecular sieve in the obtained catalyst is 80wt%.
[0131] Example 16
[0132] The preparation process of the catalyst is as follows: 64.1 grams of magnesium nitrate hexahydrate are added to 200 grams of deionized water to dissolve, 130 grams of diatomaceous earth are added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 700°C for 10 hours to obtain 140 grams of modified binder (magnesium oxide weight content is 7.14%). 60 grams of HMCM-22 molecular sieve with a molar silicon-aluminum ratio of 30 and 60 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 40 are mixed with the above-mentioned 140 grams of modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0133] Dry at 120℃ and calcine at 550℃ for 4 hours. The above catalyst is cut into 1-3mm to obtain a columnar catalyst matrix S0. 20 grams of S0 sample is impregnated with nickel nitrate and zinc nitrate aqueous solution (nickel nitrate mass content is 19.46%, zinc nitrate mass content is 21.93%) for 20 hours, dried at 120℃, and calcined at 700℃ for 3 hours. The weight content of nickel oxide is 5% and the weight content of zinc oxide is 6%, thereby obtaining S1. 10g of n-hexane solution of 30% by weight ethyl orthosilicate is added to 20g of S1, immersed at room temperature for 2 hours, dried at 120℃, and calcined at 550℃ for 10 hours to obtain S2. 10g of cyclohexane solution of 20% by weight benzyl silicone oil is added to 20g of R2, immersed at room temperature for 2 hours, and dried at 120℃. The calcination procedure is the same as that of R2 to obtain R3. 20 g of S3 was placed in 200 g of 10% ammonia solution for hydrothermal treatment for 20 hours at a treatment temperature of 150° C. and calcined at 550° C. for 3 hours to obtain catalyst S. The content of molecular sieve in the obtained catalyst was 30 wt%.
[0134] Embodiment 17
[0135] The preparation process of the catalyst is as follows: 32 grams of magnesium nitrate hexahydrate are added to 100 grams of deionized water to dissolve, 55 grams of aluminum oxide are added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 600°C for 10 hours to obtain 60 grams of a modified binder (magnesium oxide weight content is 8.3%). 140 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 200 is mixed with the above 60 grams of the modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0136] Dry at 120℃ and calcine at 550℃ for 4 hours. The above catalyst was cut into 1-3mm to obtain a columnar catalyst matrix T0. 20 grams of T0 sample was impregnated with calcium nitrate and zinc nitrate aqueous solution (nickel calcium nitrate content of 8.43%, zinc nitrate mass content of 18.28%) for 24 hours, dried at 120℃, and calcine at 600℃ for 3 hours. The calcium oxide weight content was 2% and the zinc oxide weight content was 5% to obtain T1. 10g of a 30% by weight dimethyl silicone oil n-hexane solution was added to 20 grams of T1, immersed at room temperature for 2 hours, dried at 120℃, and calcine at 550℃ for 10 hours to obtain T2. 10g of a 20% by weight benzyl silicone oil cyclohexane solution was added to 20 grams of T2, immersed at room temperature for 2 hours, and dried at 120℃. The calcination procedure was the same as that of T2 to obtain T3. 20 g of T3 was placed in 200 g of 6% ammonia solution for hydrothermal treatment for 12 hours at a treatment temperature of 180° C. and calcined at 550° C. for 5 hours to obtain catalyst T. The molecular sieve content in the obtained catalyst was 70 wt%.
[0137] Embodiment 18
[0138] The preparation process of the catalyst is as follows: 32 grams of magnesium nitrate hexahydrate are added to 100 grams of deionized water to dissolve, 35 grams of kaolin are added, and the mixture is immersed at 80°C for 12 hours, dried at 120°C, and calcined at 600°C for 10 hours to obtain 40 grams of modified binder (magnesium oxide weight content is 12.5%). 160 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 100 is mixed with the above-mentioned 40 grams of modified binder, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form a strip.
[0139] Dry at 120℃ and calcine at 550℃ for 4 hours. The above catalyst is cut into 1-3mm to obtain a columnar catalyst matrix U0. 20 grams of U0 sample is impregnated with chromium nitrate and zinc nitrate solution (chromium nitrate content is 15.79% and zinc nitrate mass content is 18.28%) for 24 hours, dried at 120℃, and calcined at 600℃ for 3 hours. The weight content of chromium oxide is 3% and the weight content of zinc oxide is 5%, and U1 is obtained. 10g of n-hexane solution of 40% by weight of ethyl orthosilicate is added to 20g of U1, immersed at room temperature for 2 hours, dried at 120℃, and calcined at 550℃ for 10 hours to obtain U2. 10g of cyclohexane solution of 40% by weight of benzyl silicone oil is added to 20g of U2, immersed at room temperature for 2 hours, and dried at 120℃. The calcination procedure is the same as that of U2 to obtain U3. 20 g of U3 was placed in an autoclave containing 200 g of 8% ammonia solution, sealed, and subjected to hydrothermal treatment for 15 hours at a treatment temperature of 160° C. and calcined at 550° C. for 3 hours to obtain catalyst U. The molecular sieve content in the obtained catalyst was 80%.
[0140] Embodiment 19
[0141] The preparation process of the catalyst is as follows: 30 grams of alumina, 70 grams of HMCM-49 molecular sieve with a molar silicon-aluminum ratio of 50, and 100 grams of HZSM-5 molecular sieve with a molar silicon-aluminum ratio of 500 are mixed, and an appropriate amount of 10% dilute nitric acid is added as an extrusion aid to form strips. Dry at 120°C and calcine at 550°C for 4 hours. The above catalyst is cut into 1-3 mm columnar catalyst W.
[0142] Embodiment 20
[0143] The catalyst prepared in Example 1-19 was used to react carbon dioxide with dimethyl ether to produce aromatics in a fixed bed reactor, and the reaction products were analyzed by online chromatography. The gas chromatograph was Agilent 7890A, and the chromatographic column was PLOTQ. The catalyst loading was 10.0 g, and the weight space velocity of the feed dimethyl ether was 0.3-10 h -1 , carbon dioxide: dimethyl ether = 0.5:1-20:1, reaction pressure is 0.2-10.0MPa; reactor reaction temperature is 400-600°C, under the reaction conditions of the embodiment, the conversion rate of dimethyl ether is 100%, and the reaction results of the catalyst reaction for 72 hours in various embodiments are listed in Table 1.
[0144] Aromatic selectivity = (mass fraction of aromatics in the discharge) ÷ (total mass fraction of materials in the discharge) × 100%
[0145] Table 1 Reaction conditions and reaction performance
[0146]
[0147]
[0148] Examples 21-24
[0149] The catalyst evaluation device and test method are the same as those in Example 19. The reaction catalyst loading is 100.0 g. The feed dimethyl ether weight space velocity is 1.0 h -1 , the ratio of carbon dioxide to dimethyl ether in the fresh feed was 10:1, and the reaction pressure was 8.0 MPa. The conversion rate of dimethyl ether was 100% during the reaction time, and no signs of catalyst deactivation were observed. The reaction results of the catalysts in the examples are listed in Table 2.
[0150] Table 2 Reaction performance of catalysts
[0151] Example catalyst Reactor temperature / ℃ Operation time / h Aromatic selectivity / % 21 D 470 2000 98 22 G 480 2200 97 23 N 470 2000 96 24 P 460 2200 98
[0152] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for producing aromatics from carbon dioxide and dimethyl ether, characterized in that: The following steps are involved: Passing a raw gas containing carbon dioxide and dimethyl ether into a reactor to contact with a catalyst for reaction to obtain the aromatic hydrocarbons; The catalyst is obtained by molding a material containing a molecular sieve and a binder, calcining it, and modifying it; The modification is oxide modification, silanization agent modification and hydrothermal treatment; The oxide i in the oxide i modification is selected from at least one of magnesium oxide, calcium oxide, zirconium oxide, zinc oxide, chromium oxide, and nickel oxide; The content of magnesium oxide, calcium oxide, zirconium oxide, zinc oxide, chromium oxide and nickel oxide in the catalyst is independently 1-15wt%; The silanization agent in the silanization agent modification is selected from at least one of ethyl orthosilicate, benzyl silicone oil, and dimethyl silicone oil; The binder is selected from at least one of boehmite, alumina, diatomaceous earth, silicon oxide and kaolin; The binder is a modified binder obtained by modification with oxide ii; The oxide ii in the oxide ii modification is selected from at least one of magnesium oxide, calcium oxide, zirconium oxide, zinc oxide, chromium oxide, and nickel oxide; The content of magnesium oxide, calcium oxide, zirconium oxide, zinc oxide, chromium oxide and nickel oxide in the modified binder is independently 1-25wt%; The molecular sieve is at least one of ZSM-5 molecular sieve, MCM-22 molecular sieve and MCM-49 molecular sieve; The molecular sieve has a molar silicon-to-aluminum ratio of 20-500; The molecular sieve is a hydrogen type molecular sieve or an ammonium type molecular sieve.
2. The method according to claim 1, characterized in that The molar ratio of carbon dioxide to dimethyl ether is 0.5:1-20:
1.
3. The method according to claim 1, characterized in that The feed weight space velocity of dimethyl ether is 0.3-10h -1 .
4. The method according to claim 1, characterized in that: The reaction temperature is 400-600°C.
5. The method according to claim 1, characterized in that The reaction pressure is 0.2-10.0 MPa.
6. The method according to claim 1, characterized in that The molecular sieve content in the catalyst is 30-85wt%.
7. The method according to claim 1, characterized in that The calcination i is calcined at 550° C.-700° C. for 4-10 hours.
8. The method according to claim 1, characterized in that The silanization agent modification comprises the following steps: impregnating the catalyst in a silanization agent solution and calcining ii; The solvent in the silanization agent solution is selected from cyclohexane and / or n-hexane; The content of the silanization agent in the silanization agent solution is 20-50 wt %.
9. The method according to claim 8, characterized in that The dipping time is 2-24 hours; The calcination ii is carried out at 550° C.-700° C. in an air atmosphere for 1-10 hours.
10. The method according to claim 1, characterized in that The hydrothermal treatment comprises: hydrothermally treating the catalyst in an aqueous ammonia solution; The concentration of the aqueous ammonia solution is 5-10wt%.
11. The method according to claim 1, characterized in that: The temperature of the hydrothermal treatment is 60°C-180°C, and the time is 10-24 hours.
Citation Information
Patent Citations
Gaseous phase etherifying production method of complex ether with mixed phenol methanol
CN109942383A
Process for the conversion of synthesis gas to olefins
US20130197288A1
Two stage process for improving the catalyst life of zeolites in the synthesis of lower olefins from alcohols and their ether derivatives
US4554260A